The “Sardinian cold-water coral province” in the context of the Mediterranean coral ecosystems - Taviani, M.; Angeletti, L.; Canese, S.; CANNAS, RITA; Cardone, F.; CAU, ANGELO; CAU, ALESSANDRO; FOLLESA, MARIA CRISTINA; Marchese, F.; Montagna, P.; Tessarolo, C. (Deep Sea Research Part II: Topical Studies in Oceanography, 2017)
A new cold-water coral (CWC) province has been identified in the Mediterranean Sea in the Capo Spartivento canyon system offshore the southern coast of Sardinia. The ‘Sardinia cold-water coral pro- vince’ is characterized in the Nora canyon by a spectacular coral growth dominated by the branching scleractinian Madrepora oculata at a depth of 380–460 m. The general biohermal frame is strengthened by the common occurrence of the solitary scleractinian Desmophyllum dianthus and the occasional presence of Lophelia pertusa. As documented by Remotely Operated Vehicle survey, this area is a hotspot of megafaunal diversity hosting among other also live specimens of the deep oyster Neopycnodonte zibrowii. The new coral province is located between the central Mediterranean CWC provinces (Bari Canyon, Santa Maria di Leuca, South Malta) and the western and northern ones (Melilla, Catalan- Provençal-Ligurian canyons). As for all the best developed CWC situations in the present Mediterranean Sea, the new Sardinian province is clearly influenced by Levantine Intermediate Water which appears to be a main driver for CWC distribution and viability in this basin.